Enhancing recruitment and retention of visible minority police officers in Canadian policing agencies - Rigaux, Catherine (Policing and society, 2021)
Given the challenges that police organisations continue to face in attracting visible minorities, this study reviews how minority police officers perceive the barriers they confront. The systematic review of the literature provided the initial framework to guide the interviews with 20 visible minority police officers in a medium sized police organisation in Western Canada. The results illustrate that this police organisation, like many others, is slow in changing its organisational culture. This was demonstrated through comments about some misguided recruitment practices where human resource officers are not able to generate interest from potential minority recruits. It was also demonstrated through comments about leadership’s inability to follow through on improving diversity. Thirdly, it was demonstrated through comments about job satisfaction and motivational issues. The findings point to reshaping recruitment, leadership and motivational practices as a way to better develop a more heterogeneous police culture. In re-engineering the recruitment process, a key message emphasises building relationships using ‘gatekeepers’. Changes in leadership practices might encourage transformational or shared types of leadership with structures for more engagement – teamwork, participation, and personal development. This may allow leaders and members to be involved in pursuing diversity goals and be internally motivated to carry them out. The findings also indicate that key motivators for minorities relate to community feedback, autonomy, career developmental opportunities and team relationships. These motivators build on police public service-like motivators (PSM’s) emphasising service to the larger community, a focus which might offer insights in responding to the diversity issues in the future.